2012
DOI: 10.1155/2012/256294
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-Converting Enzyme 2 (ACE2) Is a Key Modulator of the Renin Angiotensin System in Health and Disease

Abstract: Angiotensin-converting enzyme 2 (ACE2) shares some homology with angiotensin-converting enzyme (ACE) but is not inhibited by ACE inhibitors. The main role of ACE2 is the degradation of Ang II resulting in the formation of angiotensin 1–7 (Ang 1–7) which opposes the actions of Ang II. Increased Ang II levels are thought to upregulate ACE2 activity, and in ACE2 deficient mice Ang II levels are approximately double that of wild-type mice, whilst Ang 1–7 levels are almost undetectable. Thus, ACE2 plays a crucial r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
553
1
22

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 562 publications
(600 citation statements)
references
References 85 publications
(106 reference statements)
8
553
1
22
Order By: Relevance
“…According to the literature, the main substrate of ACE2 is AngII. Especially in the regulation of cardiovascular homeostasis the function of ACE2 is more important than the function of ACE because the levels of Ang II and Ang 1-7 are mainly regulated by ACE2 for balanced function of renin-angiotensin-aldosterone system (RAAS) (Tikellis and Thomas 2012). That is why we may conclude that decreased plasma level of AngII is in correlation with increased plasma level of ACE2 in N+S group.…”
Section: Discussionmentioning
confidence: 93%
“…According to the literature, the main substrate of ACE2 is AngII. Especially in the regulation of cardiovascular homeostasis the function of ACE2 is more important than the function of ACE because the levels of Ang II and Ang 1-7 are mainly regulated by ACE2 for balanced function of renin-angiotensin-aldosterone system (RAAS) (Tikellis and Thomas 2012). That is why we may conclude that decreased plasma level of AngII is in correlation with increased plasma level of ACE2 in N+S group.…”
Section: Discussionmentioning
confidence: 93%
“…ACE and ACE2 are co‐expressed in many tissues and the effects of ACE2 activity are usually opposed to those of ACE. In the kidney, ACE2 activity is reno‐protective by cleaving and thus inactivating Ang II and, at the same time, generating the protective peptide angiotensin‐(1–7) (Ang 1–7) (Tikellis and Thomas, ). In several animal models of diabetes, ACE2 expression and activity was decreased in renal tissue (Soler et al ., ; Leehey et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…In some hypertension models, it has been demonstrated that a relationship of ACE2 .ACE promotes more beneficial effects against hypertension and balances the RAS. 38,39 CONCLUSION In conclusion, TBTIF showed antihypertensive properties. These effects are related to the downregulation of ACE and the upregulation of ACE2, a reduction in the Ang I-and Ang II-induced contractility, and an increase in the vasodilator properties of Ang-(1-7) through NO-dependent and NOindependent mechanisms.…”
Section: Discussionmentioning
confidence: 78%